Analysis and Research of Several New Intelligent Optimization Algorithms - ZHANG Jiulong, WANG Xiaofeng, LU Lei, NIU Pengfei (Jisuanji kexue yu tansuo, 2022)
Intelligent optimization algorithms (IOA) refer to a kind of algorithm that is used to solve optimization problems by imitating the survival and evolution process of natural creatures or physical phenomena as the algorithm principle. The well-known intelligent optimization algorithms include genetic algorithm, particle swarm optimization, simulated annealing algorithm, etc. Intelligent optimization algorithm is a heuristic method, which is widely used in solving optimization problems and provides some new ideas for solving some practical problems. With the advan-cement of science and technology and the increase in the complexity of application scenarios, traditional intelligent optimization algorithms can no longer satisfy optimization problems in terms of solving effects and accuracy. Therefore, new and more efficient intelligent optimization algorithms are constantly being proposed. Several new intelligent optimization algorithms have been proposed at home and abroad in recent years, such as butterfly optim